Pedagogic Aspects in Nursing Education: Integrative Review - Jennifer Rojas Reyes; Luz Nelly Rivera Álvarez; María José Morera Pomarede (Universidad de Antioquia, 2018)
Objective. To know the current state of development of the thematic area of nursing education related with professional training and to determine the research trends. Methods. Descriptive integrative review, which conducted a search in databases limited from 2005 to 2016, using MeSH and DeCS terms, like Nursing, education, Nursing education research, Nursing students, health knowledge practice, and professional competence, which analyzed 50 original articles. Results. The concepts that emerged were: successful didactics, caring learning process, professional skills, professor role, and pedagogic relationships. The highest levels of evidence were found in studies on didactics; however, the trends and challenges of this review are aimed at the professional skill because it becomes the transversal concept in the formation of nurses. Conclusion. The thematic area of nursing education related with professional training has advanced in the development and level of evidence on the concept of successful didactics, which is why the other concepts have remained in exploration and description whether in quantitative or qualitative studies. All the concepts analyzed have voids and the research trend is aimed at mixed, predictive, and experimental studies that respond well to this theme.   How to cite this article: Rojas J, Rivera LN, Morera MJ. Pedagogic : Rojas J, Rivera LN, Morera MJ. Pedagogic Aspects in Nursing Education: Integrative Review. Invest. Educ. Enferm. 2018; 36(3):e03.